2017
DOI: 10.3174/ajnr.a5227
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic MRI for Clinical Neuroimaging: Results of the Magnetic Resonance Image Compilation (MAGiC) Prospective, Multicenter, Multireader Trial

Abstract: BACKGROUND AND PURPOSE: Synthetic MR imaging enables reconstruction of various image contrasts from 1 scan, reducing scan times and potentially providing novel information. This study is the first large, prospective comparison of synthetic-versus-conventional MR imaging for routine neuroimaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
226
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(241 citation statements)
references
References 25 publications
5
226
0
2
Order By: Relevance
“…Several studies have been conducted to validate the clinical feasibility of synthetic MRI . These studies reported that synthetic images such as T 1 w, T 2 w, and PDw had acceptable diagnostic utilities like that of conventional imaging series.…”
mentioning
confidence: 99%
“…Several studies have been conducted to validate the clinical feasibility of synthetic MRI . These studies reported that synthetic images such as T 1 w, T 2 w, and PDw had acceptable diagnostic utilities like that of conventional imaging series.…”
mentioning
confidence: 99%
“…[86] The synthetic FLAIR sequence had notably lower scores on image quality and more artefacts than conventional images. This is in line with other studies [54,85], reporting artefacts in FLAIR images especially in the interface between CSF and brain tissue, which makes it necessary to carefully assess the other sequences in order to classify these changes as artefacts and not pathological changes. These kinds of artefacts could be attributed to the difficulty of segmenting voxels containing two types of tissues, CSF and brain parenchyma, which is often the case in the interface of ventricle walls and at the sulci.…”
Section: Paper Isupporting
confidence: 60%
“…A more recent study with a later version of the sequence for synthetic MR showed improved numbers, with 96% of synthetic images being rated as sufficient, compared to 98% for conventional images. [85] Tanenbaum et al had a larger patient cohort with a wider range of diagnoses than our study, and they found that overall diagnostic image quality of synthetic images was statistically noninferior to conventional images. Synthetic T1WI had higher lesion conspicuity than conventional T1WI, possibly due to the higher contrast, and this could explain the higher number of correct diagnoses in synthetic T1WI.…”
Section: Paper Imentioning
confidence: 70%
See 2 more Smart Citations